BIOM-21. THE SIGNIFICANCE OF TERT PROMOTER MUTATIONS, TELOMERE LENGTH AND MGMT PROMOTER METHYLATION IN NEWLY DIAGNOSED AND RECURRENT IDH-WILDTYPE GLIOBLASTOMA (GBM): A LARGE MONO-INSTITUTIONAL STUDY. (12th November 2021) - Lombardi, Giuseppe; Giunco, Silvia; Cavallin, Francesco; Angelini, Chiara; Caccese, Mario; Cerretti, Giulia; De Bonis, Pasquale; De Rossi, Anita; Zagonel, Vittorina
Abstract: BACKGROUND: the significance of TERT promoter mutations, telomere length and their interactions with MGMT methylation status in patients with IDH-wildtype GBM patients remain unclear. We performed a monoinstitutional study to better investigate their impact and their interaction on clinical outcomes. METHODS: TERTmutations (C228T and C250T), relative telomere length (RTL) and MGMT methylation were assessed in 278 newly-diagnosed and in 65 recurrent IDH-wildtype GBM PTS which were treated from Dec2016 to Jan2020. We explored association between gene characteristics and neuroradiological response, PFS, OS. Telomere length was measured by monochrome multiplex PCR and RTL values were calculated as a telomere/single-copy gene ratio. RESULTS: characteristics of newly diagnosed GBM PTS were: median age 63 ys, ECOG PS0-1 in 71% of PTS, radical surgery in 38%, 78% received radiation therapy plus TMZ, MGMTmet in 53%, TERT promoter was mutated in 80% (75% C228T, 25% C250T), median RTL was 1.57 (range 0.4-11.37). ORR was reported in 15% of PTS, medianOS was 15 ms (95% CI 13-18 ms), medianPFS was 8 ms (95% CI 7-9 ms). At multivariable analysis, TERT mutations and RTL were not associated with clinical outcomes; about OS, TERT mutations and RTL reported a HR of 1.05 (95% CI 0.64-1.64) and 0.99 (95% CI 0.89-1.10), respectively; MGMTmet tumors showed significant improved PFS and OS with a HR of 0.54(95% CI 0.40-0.71) and 0.47 (95% CI 0.34-0.64), respectively. All interactions among MGMT-status, TERT-mutation status and RTL were not statistically significant. Characteristics of recurrent GBM PTS were: median age 55 ys, ECOG PS0-1 in 60% of PTS, MGMTmet in 37%, TERT mutations in 75% (75% C228T, 25% C250T), RTL was 1.67 (range 0.68-8.87). At multivariable analysis, only MGMTmet tumors resulted significantly associated to prolonged OS(HR0.16;95%CI0.07-0.40). No gene interaction was significant. CONCLUSIONS: we analyzed the impact of TERT mutations, RTL and MGMT in newly diagnosed and recurrent IDH-wildtype GBM PTS. TERT status and RTL were not associated with clinical outcomes. MGMT was the only prognostic factor. No significant interaction was demonstrated between TERT mutations, RTL and MGMT